Respuesta :
Answer:
x = -2 or x = 1/2
Step-by-step explanation:
First get the eq in standard form, which means:
x² should not have that 2 in front of it
move the other 2 to the left
so first let's divide by 2:
x² + 3/2 x = 1
now move the 1 to the left
x² + 3/2 x - 1 = 0
now look for two numbers that, when multiplied, give -1, and when added, give 3/2. This is a bit of trial-and-error if you want to solve in this way.
The numbers are 2 and -1/2, since 2*-1/2 = -1, and 2 - 1/2 = 3/2
The factorization thus is:
x² + 3/2 x - 1 = (x+2)(x-1/2) = 0
Either factor (x+2) or (x-1/2) can be zero to solve the solution, hence x = -2 or x = 1/2
Answer:
x = - 2, x = [tex]\frac{1}{2}[/tex]
Step-by-step explanation:
Given
2x² + 3x = 2 ( subtract 2 from both sides )
2x² + 3x - 2 = 0
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term
product = 2 × - 2 = - 4 and sum = + 3
The factors are + 4 and - 1
Use these factors to split the x- term
2x² + 4x - x - 2 = 0 ( factor the first/second and third/fourth terms )
2x(x + 2) - 1(x + 2) = 0 ← factor out (x + 2) from each term
(x + 2)(2x - 1) = 0
Equate each factor to zero and solve for x
x + 2 = 0 ⇒ x = - 2
2x - 1 = 0 ⇒ 2x = 1 ⇒ x = [tex]\frac{1}{2}[/tex]